Food and agribusiness yearbook '97. - University of Asia and the Pacific (Pasig City University of Asia and the Pacific, 1997)
Purpose: To "provide comprehensive and relevant information necessary for the sustained growth of this significant sector and an extensive agribusiness-oriented directory for buyers, entrepreneurs, farmers, and businessmen to help them make the most of their enterprise.
Contents: Guides to tables. Index to advertisers. Philippine economy and population. Agribusiness. Food market. Commodity profiles. Trade. Exports. Imports. Kompass directory of selected. Food and agribusiness companies.
"A joint publication of the University of Asia and the Pacific and Belgosa Publishing Inc."
Keywords: Agriculture -- Economic aspects -- Philippines -- Statistics; Food industry and trade -- Philippines -- Statistics; Agricultural industries -- Philippines -- Statistics; Farm produce -- Philippines -- Statistics; Food industry and trade -- Statistics. -- Philippines; Produce trade -- Statistics. -- Philippines